manual_analysis_nomans0315_realtime - Baumgartner, Mark F.; Bonnell, Julianne; Van Parijs, Sofie M.; Corkeron, Peter J.; Hotchkin, Cara; Ball, Keenan; Pelletier, Léo-Paul; Partan, Jim; Peters, Don; Kemp, John; Pietro, Jeff; Newhall, Kris; et al. (Dryad Digital Repository, 2019)
Near real-time whale occurrence estimates for the 2015-2016 DMON/LFDCS buoy